Telegramas de felicitación para Roberto H. Todd - Todd, Roberto H.; Tous Soto, José; Castaneda, Carmelo; Díaz Llenza, L. F.; Méndez, Lumen; Torregrosa, C. F.; Ramos Casellas, V.; Pont Zayas, Fernando; Ortiz, José M.; Martínez Pena, Rafael; Schmidt, Alfredo; Hernández, Olegario; et al. (My University, 1921)
Felicitaciones por su trabajo y distinción en Washington.
Keywords: Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.; Partido Republicano (Puerto Rico)